Radiation induces EIF2AK3/PERK and ERN1/IRE1 mediated pro-survival autophagy. Issue 8 (3rd August 2019) - Chaurasia, Madhuri; Gupta, Swapnil; Das, Asmita; Dwarakanath, B.S.; Simonsen, Anne; Sharma, Kulbhushan
ABSTRACT: Cellular effects of ionizing radiation include oxidative damage to macromolecules, unfolded protein response (UPR) and metabolic imbalances. Oxidative stress and UPR have been shown to induce macroautophagy/autophagy in a context-dependent manner and are crucial factors in determining the fate of irradiated cells. However, an in-depth analysis of the relationship between radiation-induced damage and autophagy has not been explored. In the present study, we investigated the relationship between radiation-induced oxidative stress, UPR and autophagy in murine macrophage cells. A close association was observed between radiation-induced oxidative burst, UPR and induction of autophagy, with the possible involvement of EIF2AK3/PERK (eukaryotic translation initiation factor 2 alpha kinase 3) and ERN1/IRE1 (endoplasmic reticulum [ER] to nucleus signaling 1). Inhibitors of either UPR or autophagy reduced the cell survival indicating the importance of these processes after radiation exposure. Moreover, modulation of autophagy affected lethality in the whole body irradiated C57BL/6 mouse. These findings indicate that radiation-induced autophagy is a pro-survival response initiated by oxidative stress and mediated by EIF2AK3 and ERN1. Abbreviations: ACTB: actin, beta; ATF6: activating transcription factor 6; ATG: autophagy-related; BafA1: bafilomycin A1 ; CQ: chloroquine; DBSA: 3, 5-dibromosalicylaldehyde; EIF2AK3: eukaryotic translation initiation factor 2 alpha kinase 3; ERN1: endoplasmic reticulum (ER) to nucleus signaling 1; IR: ionizing radiation; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; 3-MA: 3-methyladenine; MTOR: mechanistic target of rapamycin kinase; NAC: N-acetyl-L-cysteine; PARP1: poly (ADP-ribose) polymerase family, member 1; 4-PBA: 4-phenylbutyrate; Rap: rapamycin; ROS: reactive oxygen species; UPR: unfolded protein response; XBP1: x-box binding protein 1